Comparative Analysis of Risk-Return using the Fama-French Three-Factor Model - San Andrés Reyes, Pablo Ricardo; Villena Izurieta, Nadia Priscila; Saltos Zúñiga, Patricia Elizabeth; Paredes Chévez, Ivonne Elizabeth (Revista Venezolana de Gerencia, 2026)
The article analyzes investment evaluation and cost of capital assessment techniques, emphasizing that the Fama-French Three-Factor Model provides a more accurate estimate than the traditional CAPM. The study applied this methodology to two companies in the entertainment sector listed on the New York Stock Exchange: Walt Disney Company and United Parks & Resorts, during the period 2013-2024.The results of the multiple regressions showed that United Parks & Resorts had a better statistical fit with an R² of 22.10%, compared to 14.78% for Disney, indicating greater predictive power. The annual cost of capital was 153% for Disney and 137% for United Parks & Resorts, reflecting different risk-return profiles. The analysis revealed that United Parks is more sensitive to factors such as company size and stock value, while Disney is more resistant to these systematic risks. The authors conclude that the Fama-French model offers more reliable information for investment decisions by incorporating multiple economic factors, allowing investors to select companies based on their risk tolerance.